Isolation of a Clostridium Beijerinckii sLM01 cellulosome and the effect of sulphide on anaerobic digestion - Mayende, Lungisa (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2007)
Cellulose is the most abundant and the most resistant and stable natural organic compound on earth. Enzyme hydrolysis is difficult because of its insolubility and heterogeneity. Some (anaerobic) microorganisms have overcome this by having a multienzyme system called the cellulosome. The aims of the study were to isolate a mesophilic Clostridium sp. from a biosulphidogenic bioreactor, to purify the cellulosome from this culture, to determine the cellulase and endoglucanase activities using Avicel and carboxymethylcellulose (CMC) as substrates and the dinitrosalicyclic (DNS) method. The organism was identified using 16S rDNA sequence analysis. The sequence obtained indicated that a strain of Clostridium beijerinckii was isolated. The cellulosome was purified from the putative C. beijerinckii sLM01 host culture using affinity chromatography purification and affinity digestion purification procedures. The cellulosomal and non-cellulosomal fractions of C. beijerinckii sLM01 were separated successfully, but the majority of the endoglucanase activity was lost during the Sepharose 4B chromatography step. These cellulosomal and non-cellulosomal fractions were characterised with regards to their pH and temperature optima and effector sensitivity. Increased additions of sulphide activated the cellulase activity of the cellulosomal and non-cellulosomal fractions up to 700 %, while increased additions of sulphate either increased the activity slightly or inhibited it dramatically, depending on the cellulosomal and non-cellulosomal fractions. Increased additions of cellobiose, glucose and acetate inhibited the cellulase and endoglucanase activities. pH optima of 5.0 and 7.5 were observed for cellulases and 5.0 for endoglucanases of the cellulosomal fraction. The noncellulosomal fraction exhibited a pH optimum of 7.5 for both cellulase and endoglucanase activities. Both fractions and enzymes exhibited a temperature optimum of 30 Â°C. The fundamental knowledge gained from the characterisation was applied to anaerobic digestion, where the effect of sulphide on the rate-limiting step was determined. Sulphide activated cellulase and endoglucanase activities and increased the % chemical oxygen demand (COD) removal rate. Levels of volatile fatty acids (VFAs) were higher in the bioreactor containing sulphide, substrate and C. beijerinckii. Sulphide therefore accelerated the rate-limiting step of anaerobic digestion.
Keywords: Cellulose; Clostridium; Cellulase; Sulfides